Predictors of UK healthcare worker burnout during the COVID-19 pandemic - Ferry, A V (QJM, 2020)
BACKGROUND: The COVID-19 pandemic is putting health professionals under increasing pressure. This population is already acknowledged to be at risk of burnout. AIM: We aim to provide a ‘snapshot’ of the levels of burnout, anxiety, depression and distress among healthcare workers during the COVID-19 pandemic. METHODS: We distributed an online survey via social media in June 2020 open to any UK healthcare worker. The primary outcome measure was symptoms of burnout measured using the Copenhagen Burnout Inventory. Secondary outcomes of depression, anxiety, distress and subjective measures of stress were also recorded. Multivariate logistic regression analysis was performed to identify factors associated with burnout, depression, anxiety and distress. RESULTS: A total of 539 persons responded to the survey; 90% female and 53% nurses. Participants with moderate-to-severe burnout were younger (49% vs. 33% under 40 years, P = 0.004), more likely to have pre-existing comorbidities (21% vs. 12%, P = 0.031), twice as likely to have been redeployed from their usual role (22% vs. 11%; P = 0.042), or to work in an area dedicated to COVID-19 patients (50% vs. 32%, P < 0.001) and were almost 4 times more likely to have previous depression (24% vs. 7%; P = 0.012). CONCLUSION: Independent predictors of burnout were being younger, redeployment, exposure to patients with COVID-19, being female and a history of depression. Evaluation of existing psychological support interventions is required with targeted approaches to ensure support is available to those most at risk.